Temporal Aspects of the Association between Exposure to the World Trade Center Disaster and Risk of Cutaneous Melanoma - Paolo Boffetta; David G. Goldfarb; Rachel Zeig-Owens; Dana Kristjansson; Jiehui Li; Robert M. Brackbill; Mark R. Farfel; James E. Cone; Janette Yung; Amy R. Kahn; Baozhen Qiao; Maria J. Schymura; et al. (Elsevier, 2022)
Rescue/recovery workers who responded to the World Trade Center (WTC) attacks were exposed to known/suspected carcinogens. Studies have identified a trend toward an elevated risk of cutaneous melanoma in this population; however, few found significant increases. Furthermore, temporal aspects of the association have not been investigated. A total of 44,540 non-Hispanic White workers from the WTC Combined Rescue/Recovery Cohort were studied between March 12, 2002 and December 31, 2015. Cancer data were obtained through linkages with 13 state registries. Poisson regression was used to estimate hazard ratios and 95% confidence intervals using the New York State population as the reference; change points in hazard ratios were estimated using profile likelihood. We observed 247 incident cases of melanoma. No increase in incidence was detected during 2002-2004. From 2005 to 2015, the hazard ratio was 1.34 (95% confidence interval = 1.18-1.52). A dose‒response relationship was observed by arrival time at the WTC site. Risk was elevated just over 3 years after the attacks. Whereas WTC-related exposures to UVR or other agents might have contributed to this result, exposures other than those at the WTC site, enhanced medical surveillance, and lack of a control group with a similar proportion of rescue/recovery workers cannot be discounted. Our results support continued study of this population for melanoma.